Rate of force development and electromechanical delay are negatively impacted by 6 weeks of stretch training - Bray, N. W.; Simpson, C. L.; Jakobi, J. M. (21st Annual Congress of the European College of Sport Science (ECSS), Vienna, 6. -9. July 2016, 2016)
Introduction: Previous literature has shown a negative impact on rate of force development (RFD) and electromechanical delay (EMD) of a maximal voluntary contraction (MVC) that follows acute bouts of static stretching (Costa et al., 2010, Esposito et. al., 2011). It is unknown whether chronic stretch training similarly impacts the neural and mechanical components of force development. The purpose of this study was to evaluate the effects of 6 weeks of chronic stretch training of the plantar flexors and Achilles tendon on RFD and EMD of plantar flexion MVCs. Methods: Five days per week for 6 consecutive weeks, the non-dominant leg of 11 males (age 22±3 years) was rotated to maximal dorsiflexion and passively stretched against a progressively increased load (20-60% MVC) for 3 minutes. At baseline, three weeks, six weeks and one week post training electromyography (EMG) was collected from the lateral and medial gastrocnemius and soleus while plantar flexor force was measured on a dynamometer with the ankle angle set to 10° of dorsiflexion. Supramaximal stimuli was administered during contraction to assess voluntary activation. EMD, RFD, EMG and the H/M Ratio (H-reflex/M-wave) were assessed from the force and EMG tracings. Results: Thirty sessions of stretch training of the plantar flexors and Achilles tendon resulted in a significant slowing of the RFD (time main effect: F(3.102)=2.280, p=0.04) from baseline at week 6 (p=0.01) and post training (p=0.02). The EMD of MVC increased (time main effect: F(33,57)=3.354, p=0.03) post training when compared to baseline (p=0.006) and week 3 (p=0.05). There was a time main effect (F1.632,386.888)=11.617, p<0.001) for normalized EMG as the amplitude decreased from baseline at week 3 (p=0.001), week 6 (p<0.001) and post training (p=0.006). There were no interactions or main effects for H/M ratio. There were no changes in the control leg (p>0.08). Discussion: Six weeks of progressively loaded chronic stretch training slowed the RFD and normalized EMG while increasing EMD of the plantar flexors during plantar flexion MVC. These results suggest that chronic stretch training interrupted activation patterns of the plantar flexors and slowed signal transmission in the muscle while leaving neural mechanisms, reflex activity and voluntary activation, unaffected. Meaning, alterations in RFD and EMD post-intervention are the result of mechanical adaptations in the muscle-tendon unit (MTU). ABSTRACT FROM AUTHOR